HEnRiE - naprava za rehabilitacijo roke in prijemanja z njo - Podobnik, Janez (Rehabilitacija (Ljubljana), 2008)
Background: Robot-assisted rehabilitation is a rehabilitation technique that uses new technologies from the field of haptic interfaces and virtual environments. It provides repetitive training and also new and interesting tasks in computer-generated virtual environments. Measurements of forces and positions acquired during the tasks allow quantitative assessment of neuro-motor state of the patients and their progress. Methods: This paper presents the HEnRiE device (Haptic environment for reaching and grasping exercises), which is primarily intended for use in robot-aided neurorehabilitation and for training of reaching, grasping and transporting virtual objects in haptic environments. The system combines haptic interface and module for grasping mounted on top of the haptic interface. With the module for grasping subjects can grasp and manipulate virtual objects. This allows combined training of upper extremity movements and grasping. Two tasks that combine upper extremity movements and grasping are presented: a pick and place task, and a winded tube. Results: The paper presents preliminary results acquired in healthy subjects for two tasks. The results we obtained with our device were compared to similar experiments from literature associated with studies of reaching and grasping. During the pick and place task, results show that healthy subjects adopt same principles for reaching and grasping in virtual environments as in real situations. During the winded tube task the haptic feedback is used to ensure that the user applies a sufficiently large force which must not be lower than reference grasp force to successfully complete the task. Conclusions: The HEnRiE device allows combined therapy for upper extremities and grasp therapy. With the use of graphic and haptic visual environments a high level of reality is achieved, which is beneficial for the motivation of the users.
Keywords: rehabilitacija; vocational rehabilitation; roka; gibanje